Changes in T Cells After ABO-Incompatible Liver Transplantation. (4th July 2017) - Kim, Jong Man; Kwon, Choon Hyuck David; Joh, Jae-Won; Choi, Gyu-Seong; Park, Jae Berm; Kang, Eun-Suk; Kim, Sung Joo; Lee, Suk-Koo
ABSTRACT: Purpose : T lymphocytes are an essential component of allograft rejection and tolerance. The aims of the present study are to analyze the characteristics of T-cell subsets between ABO-incompatible living donor liver transplantation (ABO-I LDLT) and ABO-compatible LDLT (ABO-C LDLT). Materials and Methods : Between April 2013 and June 2014, 61 patients underwent adult LDLT. ABO-I LDLT patients received rituximab and all patients received basiliximab as induction therapy and tacrolimus as maintenance therapy. The distribution of peripheral blood T lymphocyte subsets pretransplant and 4, 8, 12, and 24 weeks post-transplant were serially monitored. Results : Eight patients underwent ABO-I LDLT. Patient characteristics did not vary between the ABO-I and ABO-C groups. Absolute lymphocyte counts and CD4+ T cells in the ABO-I group were lower than those in ABO-C group after LDLT ( p =.034 and p =.039, respectively). However, the comparison between the ABO-I and ABO-C groups revealed that the CD8+ T cells, CD4/CD8 ratio, Vδ1 cells, Vδ2 cells, γδ T cells, Vδ1/Vδ2 ratio, CD3-CD56+ cells, and CD4+Foxp3+ T cells did not change significantly over time. Conclusions : Absolute lymphocyte counts and CD4+ T cell levels are different between ABO-I and ABO-C groups after LDLT. The present study suggests that T-cell lymphocyte changes in peripheral blood in ABO-I LDLT patients were similar to those in ABO-C LDLT patients.